Deadliest Enemy :Our War Against Killer Germs - Osterholam , Michael T.; Olshaker, Mark (London John Murray, 2020)
A world-leading epidemiologist shares his stories from the front lines of our war on infectious diseases and explains how to prepare for epidemics that can challenge world order. Every new development--from exploding human and animal populations to trade and travel--intensifies our susceptibility to a devastating epidemic. Ironically, a pandemic on the scale of the 1918 flu that killed perhaps a hundred million people would be deadlier today, despite a century of medical advances. As the current Zika epidemic proves, we are wholly unprepared for these diseases. So what can-and must--we do to protect ourselves against mankind's Deadliest Enemy? Separating experience-borne fact from mindless fear, Michael Osterholm and Mark Olshaker detail the plans and resources that must be in place when the unthinkable becomes the inevitable. DEADLIEST ENEMY is high scientific drama, a chronicle of mystery and discovery, a reality check, and a plan of action.
Keywords: Epidemics -- Prevention -- Communicable diseases